'E' for empire: postmodernism and imperial ideology in the context of the Sochi Olympic Games. (4th May 2018) - Anisimova, Irina
Abstract: This article discusses two cultural products associated with the Winter Olympics in Sochi 2014: the 'Russian Alphabet' video that was used as part of the opening ceremony; and the 'alternative' Olympic mascot, the blue furry frog Zoich along with its promotional campaign. The Sochi Olympics was a project intimately connected with the image of Russia as a great power. At the same time, the Games had to demonstrate Russian culture as edgy and appealing to both international and local audiences. In these videos, imperial and conservative ideology appears in a form of postmodernist fragmentation and in the guise of ironic protest art. Using these videos as a case study, I argue that the very nature of imperial ideology and postmodernist aesthetics can lead to an unexpected convergence. Unlike nationalism, rooted in modernist grand narratives of community and progress, imperial ideology has an unlimited potential for incorporating diverse and even contradictory elements. Moreover, this convergence of conservative ideology and postmodernist style results from the fact that Russian state media have adopted a version of postmodernism devoid of its progressive elements and critical content.